Governance of teaching hospitals : turmoil at Penn and Hopkins - Kastor, John A. (Johns Hopkins University Press, 2004)
"What forces lead to changes in governance among medical schools and their associated teaching hospitals? To what extent do such changes affect how well those schools and hospitals do their work? In this book, John A. Kastor, M.D., focuses on the academic medical centers of the University of Pennsylvania and the Johns Hopkins University, two institutions that underwent dramatic change in governance during the late 1990s."--Jacket